International Organization - Dr. A. Ananda Kumar (Skyfox Publishing Group, 2020)
The book studies each of the main universal international organizations. It looks at the legal rules that constitute of International, the World Trade Organization and other organizations and then considers how these rules are used in exercise to form international politics. It is common among textbooks on international organizations with its emphasis on the communication and interaction between international politics and international law. The book examine from the assumptions of international politics that cannot be understood without knowledge about international organizations, and that international organizations cannot be understood without thinking about their legal and their political features. From this statement we understood that the organizations as power players in global politics and to determine how governments are try to use them to advance their own interests. The book is to think about international organizations requires paying attention to politics, law, power and more all at once. Hence it needs theoretical thinking as well as practical experiences. The chapters in this book look at the world of global governance with an eye on these big issues and so each chapter tells stories from the details of the international organisation. This is the first edition of the book brings forward to all the viewers and it takes to update the next edition on through the rapidly changing world of international politics and law.